Upaya Meningkatkan Kemampuan Motorik Halus melalui Kegiatan Mewarnai dengan Berbagai Media - Siti Sundari; Trio Ardhian (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
Children need to get the right guidance, so as to enable them to develop their potential and abilities optimally. One of them is improving children's fine motor skills through storytelling activities. Most of the motor skills of TK/PAUD children develop less than optimally, most of the children have difficulty in thickening simple picture shapes, in many cases many children express their pictures carelessly or even get bored quickly. This is also experienced by the children of group A Kindergarten Dharma Wanita Citra Pertiwi, Josari Village, Jetis Ponorogo District. The causes of these problems are due to the lack of stimulation from the teacher, the use of media that is less attractive and also often using crayon media to express so that children become bored and children's fine motor development has not developed optimally. Therefore, researchers made observations by taking action while providing different learning to different subjects with food coloring media, and then by using food coloring media it was hoped that children would not get bored in increasing so that they could improve their fine motor skills.